Safety assessment of rice bran oil in a chicken embryo model - Atefeh Araghi; Saeed Seifi; Reza Sayrafi; Parisa Sadighara (Mashhad University of Medical Sciences, 2016)
Objective: Rice Bran Oil (RBO) is extracted from the outer layer of rice. Little information is available regarding its safety. The present study was conducted to assess its safety in chicken embryo model. Materials and Methods: RBO was injected on day 4 of incubation of chickens. The tissues and serum samples were collected. Oxidative stress parameters in the liver, kidney and brain and biochemical parameters of serum were measured. The deformities were also investigated.  Results: The changes in the liver enzymes activity were not statistically significant. There was significant decrease and increase in lipid peroxidation and glutathione level, respectively. It is suggested that RBO is a natural antioxidant source. Low-density lipoprotein cholesterol (LDL) also decreased. No abnormal findings were observed in the chickens. Conclusion: No toxic effect was observed following RBO administration in chicken embryos. This study showed that RBO is not a safety concern.